Subpubic cartilaginous cyst: an unusual cause of urinary tract infection. Issue 3 (February 2018) - Price, G; McNicholas, T; Buckingham, S; Chang, S
It is important to consider alternative causes when treating refractory cases of urinary tract infection in the elderly population.